The way things are : conversations with Huston Smith on the spiritual life - Smith, Huston; Cousineau, Phil (Berkeley : University of California Press, 2003)
Where can we find what is ultimately meaningful? How can we discover what is truly worth knowing? In one form or another Huston Smith has been posing these questions to himself--and the world--all his life. In the course of seeking answers, he has become one of the most interesting, enlightening, and celebrated voices on the subject of religion and spirituality throughout the world.
The way things are -- The primordial tradition -- Winnowing the wisdom traditions -- This is it -- The soul of the community -- Encountering God -- The place of science -- The limits of the scientific worldview -- Science as the oracle of our age -- Science, faith, and infinity -- Toward a partnership between science and religion -- The battle for the human mind -- The new paradigm -- Countering scientism -- The striking parallels -- The sacred dimensions of everyday life -- Demystifying spiritual practice -- The varieties of religious explorations -- Cleansing the doors of perception -- Fathoming psychedelic mysticism -- The wisdom of faith -- Why religion matters now more than ever.
Includes bibliographical references (pages 281-284) and index.
Print version record.
JSTOR
Keywords: Smith, Huston -- Interviews; Smith, Huston; Religion historians -- United States -- Interviews; Religion; Spiritual life; Religion and science; Religion; Religion and Science; Historiens de la religion -- États-Unis -- Entretiens; Religion; Vie spirituelle; Religion et sciences; religion (discipline); BIOGRAPHY & AUTOBIOGRAPHY -- Religious; RELIGION -- Clergy; RELIGION -- Comparative Religion; Religion; Religion and science; Religion historians; Spiritual life; United States; Spiritualiteit; Godsdienst; Wetenschap; Interview; interviews; Interviews; Interviews; Interviews